A novel risk analysis methodology to evaluate the economic performance of a biorefinery and to quantify the economic incentives for participating biomass producers. (15th February 2018) - Wang, Yu; Ebadian, Mahmood; Sokhansanj, Shahab; Webb, Erin; Zerriffi, Hisham; Lau, Anthony
Abstract: In this paper, a novel risk analysis methodology is presented to evaluate the economic performance of a biorefinery given the volatility in the market price of the final product and the variability in the biomass delivered cost. In addition, potential economic incentives for participating biomass producers are quantified for different farm participation rates. The Monte Carlo simulation model, IBSAL‐MC, is used to estimate the biomass delivered cost distribution, and a modified risk heat map is used to visualize the expected return on investment (ROI) for various combinations of the market price of the final product and the biomass delivered cost. The developed methodology is applied to an under‐construction cellulosic sugar facility located in Sarnia, southwestern Ontario. Four farm participation rates of 20% (base‐case scenario), 30%, 40% and 50% are studied. The results show that the expected annual ROI for the base‐case scenario is estimated to be 1.3%. As the farm participation rate increases, the expected annual ROI increases from 1.3% at 20% farm participation rate to 3.4%, 4.6% and 5.1% at 30%, 40% and 50% rates, respectively. At high sugar market prices ($375–$525/tonne), the overall expected annual ROI increases to 9.5%, 11.4%, 12.6% and 13.0% in 20%, 30%, 40% and 50% farm participation rates, respectively. In this case, the economic incentives to share with biomass producers are estimated to be $14.10/dry tonne (dt), $15.77/dt and $16.33/dt by increasing the farm participation rate from 20% to 30%, 40% and 50%, respectively. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd